Structural and tidal models of Titan and inferences on cryovolcanism. Issue 5 (12th May 2014) - Sohl, F.; Solomonidou, A.; Wagner, F. W.; Coustenis, A.; Hussmann, H.; Schulze‐Makuch, D.
Abstract Titan, Saturn's largest satellite, is subject to solid body tides exerted by Saturn on the timescale of its orbital period. The tide‐induced internal redistribution of mass results in tidal stress variations, which could play a major role for Titan's geologic surface record. We construct models of Titan's interior that are consistent with the satellite's mean density, polar moment‐of‐inertia factor, obliquity, and tidal potential Love number k2 as derived from Cassini observations of Titan's low‐degree gravity field and rotational state. In the presence of a global liquid reservoir, the tidal gravity field is found to be consistent with a subsurface water‐ammonia ocean more than 180 km thick and overlain by an outer ice shell of less than 110 km thickness. The model calculations suggest comparatively low ocean ammonia contents of less than 5 wt % and ocean temperatures in excess of 255 K, i.e., higher than previously thought, thereby substantially increasing Titan's potential for habitable locations. The calculated diurnal tidal stresses at Titan's surface amount to 20 kPa, almost comparable to those expected at Enceladus and Europa. Tidal shear stresses are concentrated in the polar areas, while tensile stresses predominate in the near‐equatorial, midlatitude areas of the sub‐ and anti‐Saturnian hemispheres. The characteristic pattern of maximum diurnal tidal stresses is largely compliant with the distribution of active regions such as cryovolcanic candidate areas. The latter could be important for Titan's habitability since those may provide possible pathways for liquid water‐ammonia outbursts on the surface and the release of methane in the satellite's atmosphere.